مسیحی الہیات کے تشکیلی عناصر :تاریخی و تجزیاتی مطالعہ: Formative Elements of Christian Theology: A Historical and Analytical Study - Rizwan Ilahi; Dr. Ihsan ul Rehman Ghauri (International Research Journal of Arabic and Islamic Studies, 2024)
This study explores the formative elements of Christian theology through a historical and analytical lens, focusing on the key factors that shaped its doctrinal and theological foundations. The research investigates the interplay between early Church traditions, scriptural interpretations, and philosophical influences in the development of Christian thought. It also examines the impact of socio-political contexts, ecumenical councils, and influential theologians on the evolution of core theological doctrines such as Christology, the Trinity, and Soteriology. By providing a detailed analysis of these formative elements, the study aims to offer a nuanced understanding of the historical trajectory and intellectual frameworks that underpin Christian theology. The research further discusses how these foundational elements continue to influence contemporary theological debates and Christian practices across different denominations.